The Effect of Chest Physiotherapy on Children's Quality of Life with Acute Lymphoblastic Leukemia and Pneumonia at Dr. Moewardi Hospital, Surakarta - Fikritama, Aisya; Andarini, Ismiranti; Widjaya, Sri Lilijanti (Journal of Maternal and Child Health, 2022)
Background: Acute lymphoblastic leukemia (ALL), a malignancy that is the most common form of leukemia found in children, accounting for about 30 percent of all pediatric cancer. The incidence of pneumonia is often found in children undergoing treatment for ALL. Complications of ALL and the side effects of its treatment can affect children’s quality of life. This study aimed to the effect of chest physiotherapy on  children's quality of life with acute lymphoblastic leukemia and pneumonia. Subjects and Method: This was a quasi-experiment study conducted at the pediatric ward of Dr. Moewardi Hospital Surakarta, from February to August 2021. A number of 60 children aged 2-18 years with lymphoblastic leukemia and pneumonia was selected for this study. These children were divided into two groups, (1) 30 children with chest physiotherapy (intervetion group) and (2) 30 children received standard care (control group). Patients and parents were asked to fill out a quality of life assessment using the PedsQLTM 4.0 generic module. Mean difference of quality of life before and after chest physiotherapy between intervention and control group was examined using independent t test. Results: After intervention of chest physiotherapy, quality of life score in the intervention group (Mean= 68.91; SD= 12.30) was higher than control group (Mean= 60.12; SD= 7.72), with p= 0.002. Conclusion: Chest physiotherapy improves the quality of life in children with acute lymphoblastic leukemia and pneumonia.